Observation of the decay B[bar]0→Λ+c¯pπ0 - Aubert, Bernard; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
In a sample of 467×106 BB[bar] pairs collected with the BABAR detector at the PEP-II collider at SLAC we have observed the decay B[bar]0→Λ+cp[bar]π0 and measured the branching fraction to be (1.94±0.17±0.14±0.50)×10−4, where the uncertainties are statistical, systematic, and the uncertainty on the Λ+c→pK−π+ branching fraction, respectively. We determine an upper limit of 1.5×10−6 at 90% C.L. for the product branching fraction B(B[bar]0→Σ+c(2455)p[bar])×B(Λ+c→pK−π+). Furthermore, we observe an enhancement at the threshold of the invariant mass of the baryon-antibaryon pair.